Metabolomics analysis of the effect of GnRH on the pregnancy rate of ewes with estrus synchronization scheme based on progesterone - Zhang, Jing; Sun, Shuyuan; Bai, Xinyu; Yang, Nana; Liu, Yiyong; Wu, Xinglong; Li, Xiangyun (Frontiers in Veterinary Science, 2024)
Introduction: Gonadotropin-releasing hormone (GnRH) is widely used in the timed artificial insemination protocol for sheep. However, there remains a debate regarding its impact on pregnancy rates during artificial insemination. This study aims to evaluate the effect of GnRH on the pregnancy rates in Huyang ewes, analyze the pre-implantation metabolite changes caused by GnRH using metabolomics, and elucidate the mechanism effect on pregnancy rates. Methods: All ewes were administered a vaginal progesterone sponge containing 45 mg of flurogestone acetate for 12 days and received 330 units of equine chorionic gonadotropin (eCG) intramuscularly after sponge removal. The experimental group (n = 69) received an intramuscular treatment of 17 μg GnRH agonist triptorelin48 h after sponge removal on Day 0, while the control group (n = 41) received 1 ml of sterile saline solution. All ewes underwent a single vaginal insemination 58 hours after the withdrawal of the progesterone sponge. The difference in pregnancy rates between the two groups was calculated. Metabolomic analysis was performed on plasma samples collected on Day 7 after the treatment of GnRH agonist. Results: GnRH treatment significantly reduced the pregnancy rate in the experimental group compared with the control group (72.2% vs 82.9%, P < 0.05). Metabolomic analysis indicated that GnRH treatment affected metabolites involved in collagen synthesis and prostaglandin synthesis in the endometrial tissue, which includes a marked decrease in hydroxyproline amino acid content and a significant increase in corticosterone and prostaglandin D2 lipids and unsaturated fatty acids.In summary, the injection of GnRH agonist Triptorelin 48 hours after progesterone sponges removal reduces the pregnancy rate of Huyang ewe following artificial insemination. It also affects the metabolite levels related to endometrial collagen and prostaglandin synthesis, harming embryo implantation.